Experimental Methods Improve Learning Outcomes on Human Respiratory System Material in Fifth Grade Elementary School Students - Septiana Khusnul Khotimah; Farid Ahmadi (LPPM Undiksha, 2024)
Students who feel bored in science and science learning activities impact low student learning outcomes. This research aims to analyze the influence and effectiveness of experimental methods on science and science learning outcomes regarding the respiratory system in class V elementary school. This research uses an experimental method with a quantitative approach. The design form of this research is a Nonequivalent Control Group Design. The population in this study was all fifth-grade elementary school students, totaling 121 students. The sampling technique used in this research was cluster sampling. The sample in this study was 50 students in the experimental class, 50 in the control class, and the remaining 21 in the test class. The methods used to collect data are tests, observation, interviews, documentation, and field notes. The instruments used to collect data were questionnaire sheets and test questions. The data analysis technique used in this research is inferential statistical analysis. The research results, namely the results of the t-test, show that the experimental method has an influence and is effectively used in improving the science and science learning outcomes of class V students on the human respiratory system. The results of the n-gain test showed an increase in understanding of IPAS in the control group, including in the medium category, and an increase in understanding of IPAS in the experimental group, including in the high category. It was concluded that the experimental method could improve science and science learning outcomes regarding the respiratory system in class V elementary school.